Ответы и объяснения

Лучший Ответ!
2014-03-20T10:18:19+00:00
2Mg + O2 = 2MgO
Mg(0)   -2e  = Mg(+2)         <------Коэф.2
O2  + 4e = 2O(-2)              <-----Коэф. 1
 т.к. Н.О.К.=4, Mg - восстановитель, O - окислитель.
 MgO + 2HCl = MgCL2 + H2O
MgO + 2H(+) + 2Cl(-) = Mg(2+) + 2Cl(-) + H2O
MgO+2H(+)=Mg(2+)+H2O

MgCl2 + 2NaOH = 2NaCl + Mg(OH)2
Mg(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = 2Na(+) + 2Cl(-) +Mg(OH)2
Mg(2+) + 2OH(-)=Mg(OH)2
2014-03-20T10:21:21+00:00
2Mg+O2=2MgO
Mg° -2e⁻=Mg⁺²  -окисление
Mg° -восстановитель
O₂°- окислитель
O°₂ +4e⁻=2O⁻²   -восстановление
MgO+2HCl=MgCl2+H2O
MgCl2+2NaOH=Mg(OH)2∨+2NaCl
Mg²⁺ + 2Cl⁻ +2Na⁺ + 2OH⁻=Mg(OH)2 + 2Na⁺+2Cl⁻
Mg²⁺ + 2OH⁻=Mg(OH)2